The Influence of Leadership Style, Organizational Culture, and Teacher Commitment on Student Cooperative Performance - Tasmiah Tasmiah; Elpisah Elpisah; Rego Devilla; Suarlin Suarlin (International Journal of Social Science and Humanity, 2025)
This study aims to (1) analyze the influence of the principal’s leadership style on the performance of student cooperative managers at SMP Negeri 21 Makassar; (2) assess the influence of organizational culture; (3) examine the impact of teacher commitment; (4) analyze the simultaneous effect of leadership style, organizational culture, and teacher commitment; and (5) identify the most dominant influencing variable. This quantitative research involved 45 student cooperative managers from grades VII–IX using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple regression, t-test, and F-test with SPSS 26. Results show that leadership style, organizational culture, and teacher commitment have a significant positive partial and simultaneous effect. Teacher commitment is the most dominant variable influencing cooperative management performance.